Comparing Between Production Scheduling Methods to Achieve Efficient Resource Utilization - Nursanti, Ellysa; Sibut, Sibut; Jayabalan, Sudharsan; Handoko, Fourry; Oktarina, Nindya (Institut Teknologi Sepuluh Nopember, 2020)
High competition among industries nowadays, requires companies to improve their production services. The speed of production service time, with excellent quality, becomes part of the company’s competitive advantage. This study aims to compare several production scheduling methods which are commonly used, so that efficient resource utilization can be obtained. Production Scheduling Methods such as Make to Order, Dannenbring, Branch and Bound, Nawaz Enscore and Ham and Campbell Dudeck Smith were compared using one case of tire retreading production. There were two jobs: tire retreading for truck and bus. Each job, assigned to ten workstations following its production steps. The results were obtained that Dannenbring and Campbell Dudeck Smith gave the same best results with the smallest makespan value, equivalent to 48% efficiency.